2015
DOI: 10.1007/s12026-015-8625-5
|View full text |Cite
|
Sign up to set email alerts
|

SEW2871 protects from experimental colitis through reduced epithelial cell apoptosis and improved barrier function in interleukin-10 gene-deficient mice

Abstract: Loss of intestinal epithelial barrier function including typical tight junction changes and epithelial cell apoptosis plays an important role in Crohn's disease. SEW2871, a selective sphingosine-1-phosphate type-1 receptor agonist, has been proven to be efficient in protecting against colitis in IL-10(-/-) mice in our previous study. Here we performed additional studies to investigate whether treatment with SEW2871 was associated with an improved epithelial barrier function in IL-10(-/-) mice. SEW2871 was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Western blotting of protein expressions was performed in details as described previously [34, 35]. The primary antibodies against TAK1, IKK-α, IkB-α and p65 were all purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting of protein expressions was performed in details as described previously [34, 35]. The primary antibodies against TAK1, IKK-α, IkB-α and p65 were all purchased from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigated the influence of S1PR1 agonists on EC barrier protection in various different disease models with mixed results. While some studies showed beneficial effects [7,25], others reported they were ineffective [26]. Thus far, even successful approaches with S1PR1 agonists were not very effective.…”
Section: Discussionmentioning
confidence: 99%
“…This barrier-protective effect of S1P was attributed to an increase in level and distribution of E-cadherin (18). Recent studies showed that oral treatment of S1P agonist protected experimental colitis by improving tight junction-dependent barrier function (11). However, there are no studies pertaining to its effects on intestinal epithelial absorptive processes, which are fundamental to diarrhea associated with IBD (33).…”
Section: Discussionmentioning
confidence: 99%
“…S1P is known to regulate the gut immune system in both health and disease states (22) and has been reported to inhibit gastrointestinal injury in response to radiation or chemically induced colitis (4). This protection was conferred via sphingosine-1-phosphate receptor (S1PR) signaling at least in colitis (11). But mechanistic details of the underlying processes are not well understood.…”
mentioning
confidence: 99%